2009
DOI: 10.1007/s10800-009-9903-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved performances of mechanical-activated LiMn2O4/MWNTs cathode for aqueous rechargeable lithium batteries

Abstract: LiMn 2 O 4 /multi-walled carbon nanotubes (MWNTs) composite was synthesized by mechanical activation reaction followed by a heat-treatment (500°C). The LiMn 2 O 4 and LiMn 2 O 4 /MWNTs as cathodes were investigated in 1 M Li 2 SO 4 by cyclic voltammetry (CV), galvanostatic charge/discharge (GC), and electrochemical impedance spectroscopy (EIS). The LiMn 2 O 4 /MWNTs cathode delivered higher discharge capacity (117 mAh g -1 ) than LiMn 2 O 4 (84.6 mAh g -1 ). Furthermore, the results from EIS showed that LiMn 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Zhang et al prepared LiMn2O4/MWNTs composite by a ball-milling process with a high temperature treatment at 500 °C for 1 h [66], the morphology of the prepared LiMn2O4/MWNTs composite is shown in Figure 5a The LiMn2O4/MWNTs cathode was investigated in 1 mol·L −1 Li2SO4 for aqueous rechargeable batteries and it delivered higher discharge capacities than the LiMn2O4 cathode at different current densities (Figure 5b). Moreover, the results from electrochemical impedance spectroscopy (EIS) revealed that the transfer of Li ions in the LiMn2O4/MWNTs cathode CNTs possess unusual properties, including exceptionally high mechanical strength and high electrical conductivity.…”
Section: Limn2o4/cnt Nanocompositesmentioning
confidence: 99%
“…Zhang et al prepared LiMn2O4/MWNTs composite by a ball-milling process with a high temperature treatment at 500 °C for 1 h [66], the morphology of the prepared LiMn2O4/MWNTs composite is shown in Figure 5a The LiMn2O4/MWNTs cathode was investigated in 1 mol·L −1 Li2SO4 for aqueous rechargeable batteries and it delivered higher discharge capacities than the LiMn2O4 cathode at different current densities (Figure 5b). Moreover, the results from electrochemical impedance spectroscopy (EIS) revealed that the transfer of Li ions in the LiMn2O4/MWNTs cathode CNTs possess unusual properties, including exceptionally high mechanical strength and high electrical conductivity.…”
Section: Limn2o4/cnt Nanocompositesmentioning
confidence: 99%
“…It is noteworthy that LiMn 2 O 4 /conductive carbon composites have aroused considerable interest in recent years owing to their enhancing effect on electrical conductivity and thereby on rate capability and cycling stability. The composite materials studied include LiMn 2 O 4 /CNTs [9][10][11][12][13][14][15], LiMn 2 O 4 /graphene [15,16] and LiMn 2 O 4 /acetylene black [17]. It is well known that LiMn 2 O 4 is commonly prepared in air atmosphere at a higher temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Among these cathode materials, LiMn 2 O 4 with the merits of abundant manganese resources, low cost, low toxicity, and high stability, is a most promising candidate cathode material. It has been proved that LiMn 2 O 4 electrode has excellent cycle performance [13,14]. Tian et al [13] investigated the electrochemical properties of spinel LiMn 2 O 4 in 5 M aqueous LiNO 3 solution and found LiMn 2 O 4 had high capacity retention of 71.2% after 600 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al [13] investigated the electrochemical properties of spinel LiMn 2 O 4 in 5 M aqueous LiNO 3 solution and found LiMn 2 O 4 had high capacity retention of 71.2% after 600 cycles. Chen et al [14] reported that the discharge capacity of LiMn 2 O 4 in 1 M aqueous Li 2 SO 4 solution for the first cycle was 84.6 mAh g À1 at 0.1 A g À1 , and decreased to 50.1 mAh g À1 after 1000 cycles. It is noted that these data were obtained using a three-electrode cell, in which a platinum (or activated carbon) electrode as counter electrode and saturated calomel electrode (SCE) as reference electrode.…”
Section: Introductionmentioning
confidence: 99%